2022
DOI: 10.30541/v55i2pp.123-149
|View full text |Cite
|
Sign up to set email alerts
|

Do Workers’ Remittances Boost Human Capital Development?

Abstract: This study examines the influence of workers’ remittances along with the economic governance system on human capital development in 17 countries having low income, lower middle, upper middle and high income levels by using the annual panel between 1996 and 2013. Overall, results of fixed-effects model reveal that workers’ remittances have significantly positive impact on the human capital development. Results also reveal the positive and significant impact of all selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…Another possible reason for not participating would be its diversion toward human capital development. Azam and Raza () have reported considerable diversion of works’ remittances of Pakistan towards human capital development, and concluded significant positive effect of remittances on human capital development . Similarly, the diversion of domestic savings towards the real sector also contains remittance income from participation in capital formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible reason for not participating would be its diversion toward human capital development. Azam and Raza () have reported considerable diversion of works’ remittances of Pakistan towards human capital development, and concluded significant positive effect of remittances on human capital development . Similarly, the diversion of domestic savings towards the real sector also contains remittance income from participation in capital formation.…”
Section: Resultsmentioning
confidence: 99%
“…Cooray () investigated and found significant positive effect of workers’ remittances on domestic economic growth in South Asia through education and financial sector development. Azam and Raza () noted diversion towards human development and found a significant positive effect. In a cross‐country analysis Siddique et al () explored the nexus between the workers’ remittances and economic growth in India, Bangladesh, and Sri Lanka by using Granger causality analysis and vector autoregressive modelling analysis.…”
Section: Survey Of Literaturementioning
confidence: 98%
“…[Attanasio et al, (2017)]. It is found that if the remittances received by the household increase by one unit, it will lead to an increase in the human capital index or human capital by 0.544 units, significant statistically at a 10 percent significance level [Azam and Raza (2016)]. If the per capita income of the household increases by one percent, the human capital index or human capital of the household will increase by 0.876 units.…”
Section: Empirical Findingsmentioning
confidence: 99%
“…Results obtained in this study indicate that remittances raise per capita health expenditures and reduce undernourishment prevalence, depth of food deficit, prevalence of stunting, and child mortality rate. Azam and Raza (2016) suggested that the strong economic governance system strengthens the association between workers' remittances and human capital during the aforementioned time period. Huay, Winterton, Bani, and Matemilola (2019) revealed that the effect of remittances is statistically significant with positive coefficients in developing countries.…”
Section: Review Of Literaturementioning
confidence: 99%